The Sacramental Dimension of the Recital of Community's Faith - Navone, John (Journal of Dharma, 1984)
The, community of faith throughout the entire biblical tradition has been cal'ed to tell its story to others. Jesus affirms that those who love him will keep his word (Jn. 14:24); that the Spirit, whom the Father will send in his name, will teach us the meaning of his story and remind us of it (Jn. 14:26). Loving him means telling his story and making it our own through the gift of his Spirit. In fact, communicating his Spirit in word and deed is telling his story and giving witness to him (Jn. 16:27). Loving Jesus means keeping his commandment to love one another (Jn. 14:15); it means shar ing with others what God has done for us and is continuing to do for us through the gift of his Spirit, which motivates and impels our telling of God's goodness. Telling the story is sharing that goodness in compliance with the commandment (or law) to love one another. The lex narrandi is the obligation of the community of faith to tell of God's wonderful deeds; it demands that the goodness of his deeds be shared and communicated.